PENYADAPAN GETAH PINUS MERKUSII DENGAN MENGGUNAKAN BEBERAPA POLA SADAP DAN TINGKAT KONSENTRASI ZAT PERANGSANG - Ishak Sumantri; Wesman Endom (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Three methode for tapping pine tree resin. i.e., 3 x 4 cm, 1,5 x8 cm and Indian tapping method were investigated in Cianjur Forest District in 1988. To increase the resin yield, sulphuric acid (H2S04) with 0%, 15 %, 25 %, and 35 % con- cetratation were used. Each tapping method was applied on fourty pine trees. The results are as fallows :1.Using stimulant with the three methods of tapping increase the resin yield. 2.From the. three tapping methods applied, Indian tapping method showed the highest resin yield, i.e. 12. 72 gram/tree/day.3.Indian tapping method gives Rp 5/kg profit. This value was found by subtracting selling price (Rp, 150/kg) with production cost (Rp. 145/kg).